Integrative HPLC profiling and transcriptome analysis revealed insights into anthocyanin accumulation and key genes at three developmental stages of black rice (Oryza sativa. L) caryopsis - Mackon, Enerand; Jeazet Dongho Epse Mackon, Guibeline Charlie; Yao, Yuhang; Guo, Yongqiang; Ma, Yafei; Dai, Xianggui; Jandan, Tahir Hussain; Liu, Piqing (Frontiers in Plant Science, 2023)
Anthocyanins are plants' secondary metabolites belonging to the flavonoid class with potential health-promoting properties. They are greatly employed in the food industry as natural alternative food colorants for dairy and ready-to-eat desserts and pH indicators. . These tremendous advantages make them economically important with increasing market trends. Black rice is a rich source of anthocyanin that can be used to ensure food and nutritional security around the world. However, research on anthocyanin accumulation and gene expression during rice caryopsis development is lacking. In this study, we used high-performance liquid chromatography (HPLC) and transcriptome analysis to track the changes in anthocyanin content and gene expression at three stages of development (milk, dough, and mature). Our results showed that anthocyanin accumulation started to be visible seven days after flowering (DAF), increased rapidly from milky (11 DAF) to dough stage, then started decreasing after the peak was attained at 18 DAF. RNA-seq showed that 519 out of 14889, 477 out of 17914, and 1614 out of 18810 genes were uniquely expressed in the milky, doughy, and mature stages, respectively. We performed three pairwise comparisons: milky vs. dough, milky vs. mature, and dough vs. mature, and identified 6753, 9540, and 2531 DEGs, respectively. The DEGs' abundance was higher in milky vs. mature, with 5527 up-regulated genes and 4013 down-regulated genes, while it was smaller in dough vs. mature, with 1419 up-regulated genes and 1112 down-regulated DEGs. This result was in line with the changes in anthocyanin profiling and the expression of structural, regulatory, and transporter genes involved in anthocyanin biosynthesis, which showed their highest expression at the dough stage. Through the gene expression profile and protein interaction network, we deciphered six main contributors to the anthocyanin peak observed at dough stage, including OsANS, OsDFR, OsGSTU34, OsMYB3, OsbHLH015, and OsWD40-50. Taken together, the findings of this study revealed potential candidate genes for further genetic manipulation of anthocyanin.